Asphalt composition and asphalt composite material
By adding petroleum resin with specific weight-average molecular weight and silicon content to the asphalt composition and copolymerizing it with straight-run asphalt, the problem of insufficient water resistance of asphalt composite materials is solved, high adhesion between asphalt and aggregate is achieved, asphalt peeling is inhibited, and the service life of the road is extended.
Patent Information
- Application Number
- CN202480014627.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-28
- Filing Date
- 2024-02-26
- Publication Date
- 2025-10-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The water resistance of existing asphalt composite materials is insufficient, resulting in frequent asphalt peeling, which affects the durability and stability of roads.
By adding petroleum resin with a specific weight-average molecular weight and silicon content into the asphalt composition, the petroleum resin is copolymerized with straight-run asphalt to form an asphalt composition that can improve the adhesion between asphalt and aggregate and inhibit asphalt peeling.
Effectively inhibit asphalt stripping, improve the water resistance of asphalt composite materials, and extend the service life of roads.
Smart Images

Figure BDA0005563362670000291 
Figure BDA0005563362670000301 
Figure BDA0005563362670000302
Abstract
Description
Technical Field
[0001] The present invention relates to an asphalt composition and an asphalt composite material, and petroleum resins and hydrogenated petroleum resins used therein. Background Art
[0002] In recent years, asphalt delamination, a phenomenon in which rainwater, groundwater, and other materials penetrate between the asphalt and aggregate, peeling off the asphalt covering the aggregate surface, has become a major cause of damage to asphalt pavements. This delamination can reduce the ability to bond aggregates together, potentially leading to damage such as cracking and potholes. Consequently, research and development of asphalt compositions that can inhibit delamination have been underway.
[0003] For example, Patent Document 1 discloses a method for producing a modified hydrogenated petroleum resin, wherein a hydrogenated petroleum resin is reacted with a compound having a carbon-carbon double bond and an alkoxysilyl group in the presence of a compound that generates free radicals. Patent Document 1 also discloses an asphalt composition containing a modified hydrogenated petroleum resin and a straight-run asphalt, wherein the content of the straight-run asphalt is 70.00 to 99.99% by mass.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2021 / 161672 Summary of the Invention
[0007] Problems to be solved by the invention
[0008] Patent Document 1 has conducted research to obtain an asphalt composition capable of suppressing asphalt peeling, but there is still room for further improvement from the viewpoint of improving the water resistance of the asphalt composite material.
[0009] Therefore, an object of the present invention is to provide an asphalt composition in which the peeling of asphalt is suppressed and the water resistance of an asphalt composite material can be improved.
[0010] Means used to solve problems
[0011] The present inventors have found that the above-mentioned problems can be solved by preparing an asphalt composition containing a petroleum resin (A) and a straight-run asphalt, wherein the petroleum resin (A) contains a specific amount of silicon, has a specific weight-average molecular weight, and has a specific structure. <1> ~ <8> .
[0012] <1> An asphalt composition comprising a petroleum resin (A) and a straight-run asphalt,
[0013] The petroleum resin (A) is a petroleum resin obtained by copolymerizing monomers and silanes, wherein the monomers include at least one cyclic olefin having an ethylenically unsaturated group selected from the group consisting of C5 fraction, C8 fraction, C9 fraction obtained by decomposing naphtha, and cyclopentadiene compounds.
[0014] The petroleum resin (A) satisfies the following (a1) and (a2).
[0015] (a1) contains 0.1% by mass or more and 10% by mass or less of silicon element in terms of silicon atoms,
[0016] (a2) The weight average molecular weight (Mw) is 500 or more and 3,000 or less.
[0017] <2> According to the above <1> The asphalt composition, wherein the petroleum resin (A) satisfies the following (a3).
[0018] (a3) The softening point is 70 to 150°C.
[0019] <3> According to the above <1> or <2> In the asphalt composition, the silanes have a structure represented by the following formula (1).
[0020] Formula (1):
[0021] CH2=CR-(COO) x (C n H 2n ) y SiR'3
[0022] (In formula (1), R is a hydrogen atom or a methyl group; x and y are 0 or 1, wherein when x is 1, y is 1; n is an integer from 1 to 12; each R' is independently an alkoxy group, aryloxy group, aralkyloxy group, aliphatic acyloxy group, amino group or substituted amino group having 1 to 12 carbon atoms, or a lower alkyl group having 1 to 6 carbon atoms, wherein two or less of the three R' groups are alkyl groups.)
[0023] <4> According to the above <1> ~ <3> The asphalt composition according to any one of the preceding claims, wherein the silane is at least one selected from the group consisting of vinyltrimethoxysilane, vinyltriethoxysilane, and 3-(trimethoxysilyl)propyl methacrylate.
[0024] <5> According to the above <1> ~ <4> The asphalt composition described in any one of the preceding claims, wherein the monomers include dicyclopentadiene.
[0025] <6> According to the above <1> ~ <5> The asphalt composition according to any one of the preceding claims, wherein the petroleum resin (A) is a hydrogenated product.
[0026] <7> According to the above <1> ~ <6> The asphalt composition according to any one of the preceding claims, wherein the content of the petroleum resin (A) in the asphalt composition is 0.1% by mass or more and 5% by mass or less.
[0027] <8> Asphalt composite material containing the above <1> ~ <7> The asphalt composition and aggregate described in any one of the preceding claims, wherein the content of the asphalt composition is 1 to 20% by mass.
[0028] Furthermore, the present inventors have found that the above-mentioned problems can be solved by preparing a petroleum resin (B) containing a specific amount of silicon, having a specific weight average molecular weight and having a specific structure. <9> ~ <17> .
[0029] <9> Petroleum resin (B), which is a petroleum resin (B) obtained by copolymerizing monomers and silanes,
[0030] The monomers include at least one cyclic olefin having an ethylenically unsaturated group selected from the group consisting of C5 fraction, C8 fraction, C9 fraction obtained by decomposing naphtha and cyclopentadiene compounds.
[0031] The petroleum resin (B) satisfies the following (b1) and (b2).
[0032] (b1) contains 0.1% by mass or more and 10% by mass or less of silicon element in terms of silicon atoms,
[0033] (b2) The weight average molecular weight (Mw) is 500 or more and 3,000 or less.
[0034] <10> According to the above <9> The petroleum resin (B) mentioned above satisfies the following (b3).
[0035] (b3) The softening point is 70 to 150°C.
[0036] <11> According to the above <9> or <10> In the petroleum resin (B), the silane has a structure represented by the following formula (1).
[0037] Formula (1):
[0038] CH2=CR-(COO) x (C n H 2n ) y SiR'3
[0039] (In formula (1), R is a hydrogen atom or a methyl group; x and y are 0 or 1, wherein when x is 1, y is 1; n is an integer from 1 to 12; each R' is independently an alkoxy group, aryloxy group, aralkyloxy group, aliphatic acyloxy group, amino group or substituted amino group having 1 to 12 carbon atoms, or a lower alkyl group having 1 to 6 carbon atoms, wherein two or less of the three R' groups are alkyl groups.)
[0040] <12> According to the above <9> ~ <11> The petroleum resin (B) described above, wherein the silane is at least one selected from the group consisting of vinyltrimethoxysilane, vinyltriethoxysilane, and 3-(trimethoxysilyl)propyl methacrylate.
[0041] <13> According to the above <9> ~ <12> The petroleum resin (B) described in any one of the preceding claims, wherein the monomers include dicyclopentadiene.
[0042] <14> According to the above <9> ~ <13> The petroleum resin (B) according to any one of the preceding claims, wherein the petroleum resin (B) is a hydrogenated product.
[0043] <15> Asphalt composition containing the above <9> ~ <14> The petroleum resin (B) and straight-run asphalt described above.
[0044] <16> According to the above <15> The asphalt composition described above, wherein the content of the petroleum resin (B) in the asphalt composition is 0.1% by mass or more and 5% by mass or less.
[0045] <17> Asphalt composite material containing the above <15> or <16> The asphalt composition and aggregate, the content of the asphalt composition is 1 to 20% by mass.
[0046] Furthermore, the present inventors have found that the above-mentioned problems can be solved by preparing a hydrogenated petroleum resin (C) containing a specific amount of silicon, having a specific weight average molecular weight and having a specific structure. <18> ~ <25> .
[0047] <18> A hydrogenated petroleum resin (C) obtained by copolymerizing monomers containing at least one cyclic olefin having an ethylenically unsaturated group selected from the group consisting of a C5 fraction, a C8 fraction, a C9 fraction obtained by decomposing naphtha, and a cyclopentadiene-based compound, and silanes.
[0048] The hydrogenated petroleum resin (C) satisfies the following (c1) and (c2).
[0049] (c1) containing 0.1% by mass or more and 10% by mass or less of silicon element in terms of silicon atoms;
[0050] (c2) The weight average molecular weight (Mw) is 500 or more and 3,000 or less.
[0051] <19> According to the above <18> The hydrogenated petroleum resin (C) satisfies the following (c3).
[0052] (c3) The softening point is 70 to 150°C.
[0053] <20> According to the above <18> or <19> In the hydrogenated petroleum resin (C), the silane has a structure represented by the following formula (1).
[0054] Formula (1):
[0055] CH2=CR-(COO) x (C n H 2n ) y SiR'3
[0056] (In formula (1), R is a hydrogen atom or a methyl group; x and y are 0 or 1, wherein when x is 1, y is 1; n is an integer from 1 to 12; each R' is independently an alkoxy group, aryloxy group, aralkyloxy group, aliphatic acyloxy group, amino group or substituted amino group having 1 to 12 carbon atoms, or a lower alkyl group having 1 to 6 carbon atoms, wherein two or less of the three R' groups are alkyl groups.)
[0057] <21> According to the above <18> ~ <20> The hydrogenated petroleum resin (C) described above, wherein the silane is at least one selected from the group consisting of vinyltrimethoxysilane, vinyltriethoxysilane, and 3-(trimethoxysilyl)propyl methacrylate.
[0058] <22> According to the above <18> ~ <21> The hydrogenated petroleum resin (C) according to any one of the preceding claims, wherein the monomers include dicyclopentadiene.
[0059] <23> Asphalt composition containing the above <18> ~ <22> The hydrogenated petroleum resin (C) and straight-run asphalt described above.
[0060] <24> According to the above <23> The asphalt composition, wherein the content of the hydrogenated petroleum resin (C) in the asphalt composition is 0.1% by mass or more and 5% by mass or less.
[0061] <25> Asphalt composite material containing the above <23> or <24> The asphalt composition and aggregate, the content of the asphalt composition is 1 to 20% by mass.
[0062] Effects of the Invention
[0063] According to the present invention, it is possible to provide an asphalt composition in which peeling of asphalt is suppressed and the water resistance of an asphalt composite material can be improved. DETAILED DESCRIPTION
[0064] Hereinafter, the present invention will be described in detail, but the content of the present invention is not limited to the embodiments described below.
[0065] <Explanation of terms>
[0066] In the present invention, when expressed as "X to Y" (X and Y are arbitrary numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as the meaning of "preferably greater than X" and "preferably less than Y".
[0067] [First Invention: Asphalt Composition]
[0068] Hereinafter, the asphalt composition according to the first invention will be described.
[0069] An asphalt composition comprising a petroleum resin (A) and a straight-run asphalt,
[0070] The petroleum resin (A) is a petroleum resin obtained by copolymerizing monomers containing at least one cyclic olefin having an ethylenically unsaturated group selected from the group consisting of a C5 fraction, a C8 fraction, a C9 fraction obtained by decomposing naphtha, and dicyclopentadiene, and silanes.
[0071] The petroleum resin (A) satisfies the following (a1) and (a2).
[0072] (a1) containing 0.1% by mass or more and 10% by mass or less of silicon element in terms of silicon atoms;
[0073] (a2) The weight average molecular weight (Mw) is 500 or more and 3,000 or less.
[0074] It should be noted that the above-mentioned physical properties of the petroleum resin (A) can be appropriately adjusted by the selection of raw monomers, polymerization solvents, and catalysts, their amounts, polymerization temperature, reaction pressure, and other polymerization conditions.
[0075] The first invention provides an effect of providing an asphalt composition that suppresses asphalt peeling and improves the water resistance of an asphalt composite material. The reason for this is not necessarily certain, but it is considered as follows.
[0076] Asphalt roads are formed by the bonding of aggregates with asphalt. Aggregates are highly polar, possessing hydroxyl groups on their surfaces. Therefore, their affinity for water is even greater than their affinity for asphalt. Therefore, the presence of water hinders the adhesion between aggregates and asphalt, easily causing asphalt to peel off and, in turn, sometimes damaging asphalt roads due to the load of cars and trucks.
[0077] According to the first invention, it is believed that the hydroxyl groups on the aggregate surface react with the silane-containing groups of the petroleum resin (A) contained in the asphalt composition, thereby increasing the affinity between the aggregate and the asphalt. It is also believed that the presence of water also inhibits asphalt peeling, thereby improving the adhesion between the aggregate and the asphalt.
[0078] It should be noted that the above-mentioned mechanism related to the effects of the present invention is speculation, but the present invention is not limited thereto.
[0079] <Petroleum resin (A)>
[0080] The petroleum resin (A) satisfies the following (a1) and (a2).
[0081] (a1) containing 0.1% by mass or more and 10% by mass or less of silicon element in terms of silicon atoms;
[0082] (a2) The weight average molecular weight (Mw) is 500 or more and 3,000 or less.
[0083] The petroleum resin (A) contains silicon element in an amount of 0.1% by mass or more and 10% by mass or less, calculated as silicon atoms, preferably 0.3% by mass or more, more preferably 0.4% by mass or more, further preferably 0.5% by mass or more, still further preferably 1.0% by mass or more, further preferably 1.5% by mass or more, further preferably 2.0% by mass or more, further preferably 2.5% by mass or more, further preferably more than 2.9% by mass, further preferably 3.0% by mass or more, and preferably 8% by mass or less, more preferably 6% by mass or less, further preferably 5% by mass or less. Here, the silicon element is preferably derived from an organosilane structure.
[0084] When the silicon element concentration of the petroleum resin (A) is lower than the above range (lower than 0.3% by mass), it may be difficult to suppress the peeling of the asphalt from the aggregate.
[0085] On the other hand, if the silicon concentration of the petroleum resin (A) exceeds the above range (exceeds 10% by mass), the petroleum resin (A) may be cross-linked, and its solubility in asphalt may decrease, thereby failing to exhibit expected performance.
[0086] The silicon element concentration can be measured by ICP emission spectrometry, and specifically, can be determined by the method described in the Examples.
[0087] The weight average molecular weight (Mw) of the petroleum resin (A) is 500 or more and 3,000 or less, preferably 700 or more, more preferably 1,000 or more, further preferably 1,200 or more, and further preferably 1,300 or more, and is preferably 3,000 or less, more preferably 2,800 or less, further preferably 2,500 or less, further preferably 2,000 or less, and further preferably 1,500 or less.
[0088] When the weight average molecular weight (Mw) of the petroleum resin (A) is smaller than the above range (less than 500), the hardness at room temperature may be insufficient or the resin may become brittle, resulting in reduced strength and decreased durability as an asphalt road.
[0089] On the other hand, if the weight average molecular weight (Mw) of the petroleum resin (A) exceeds the above range (exceeds 3,000), the viscosity may increase when mixed with asphalt at high temperature, thereby deteriorating miscibility with asphalt and failing to exhibit sufficient water resistance.
[0090] In addition, from the viewpoint of improving the adhesion between aggregate and asphalt, the molecular weight distribution (Mw / Mn) of the petroleum resin (A) is preferably 5.0 or less, more preferably 4.0 or less, further preferably 3.5 or less, further preferably 3.0 or less, further preferably 2.5 or less.
[0091] The weight average molecular weight (Mw) and the number average molecular weight (Mn) are both polystyrene-equivalent molecular weights and can be measured by gel permeation chromatography (GPC). Specifically, they can be determined by the method described in Examples.
[0092] The petroleum resin (A) preferably satisfies the following (a3).
[0093] (a3) The softening point is 70 to 150°C.
[0094] From the viewpoint of improving the adhesion between aggregate and asphalt, the softening point of the petroleum resin (A) is preferably 70 to 150°C, more preferably 80 to 140°C, further preferably 90 to 140°C, and even more preferably 95 to 135°C.
[0095] In addition, the softening point can be measured according to JIS K 6863:1994.
[0096] The petroleum resin (A) preferably satisfies the following (a4).
[0097] (a4) The bromine value is 0.5 to 30 g / 100 g.
[0098] From the viewpoint of improving the adhesion between aggregate and asphalt, the bromine value of the petroleum resin (A) is preferably 0.5 to 30 g / 100 g, more preferably 1.0 to 25 g / 100 g, further preferably 2.0 to 20 g / 100 g, further preferably 3.0 to 18 g / 100 g, further preferably 3.0 to 15 g / 100 g.
[0099] In addition, the bromine value can be measured according to JIS K 2605:1996.
[0100] The petroleum resin (A) contains repeating units derived from monomers and repeating units derived from silanes, and is preferably obtained by copolymerizing monomers and silanes.
[0101] (Single type)
[0102] The monomers constituting the petroleum resin (A) include at least one cyclic olefin having an ethylenically unsaturated group selected from the C5 fraction, C8 fraction, and C9 fraction obtained by decomposing naphtha and cyclopentadiene compounds, preferably cyclopentadiene compounds, and more preferably dicyclopentadiene.
[0103] Furthermore, as monomers, it is preferable to use a cyclopentadiene compound as a first raw material and a vinyl aromatic compound as a second raw material. The first raw material may be used alone without using the second raw material.
[0104] Examples of the cyclopentadiene-based compound include cyclopentadiene, methylcyclopentadiene, ethylcyclopentadiene, and dimers and co-dimers thereof. Among these, dicyclopentadiene is preferred as the cyclopentadiene-based compound.
[0105] Examples of the vinyl aromatic compound include styrene, α-methylstyrene, β-methylstyrene, vinyltoluene, vinylxylene, indene, methylindene, and ethylindene. Among these, styrene is preferred as the vinyl aromatic compound.
[0106] The mixing ratio of the cyclopentadiene compound and the vinyl aromatic compound is not particularly limited, but is preferably cyclopentadiene compound:vinyl aromatic compound=80:20 to 20:80, more preferably 75:25 to 25:75, in terms of mass ratio.
[0107] (Silanes)
[0108] The silanes constituting the petroleum resin (A) are not particularly limited, but preferably have a structure represented by the following formula (1).
[0109] Formula (1):
[0110] CH2=CR-(COO) x (C n H 2n ) y SiR'3
[0111] (In formula (1), R is a hydrogen atom or a methyl group; x and y are 0 or 1, wherein when x is 1, y is 1; n is an integer from 1 to 12, preferably from 1 to 4; each R' is independently an alkoxy group having 1 to 12 carbon atoms (e.g., methoxy, ethoxy, butoxy), an aryloxy group (e.g., phenoxy), an aralkyloxy group (e.g., benzyloxy), an aliphatic acyloxy group having 1 to 12 carbon atoms (e.g., formyloxy, acetoxy, propionyloxy), an amino group or a substituted amino group (alkylamino, arylamino), or a lower alkyl group having 1 to 6 carbon atoms, wherein two or less of the three R' groups are alkyl groups.)
[0112] In formula (1), from the viewpoint of improving the adhesion between the asphalt composition and the aggregate, R is preferably a hydrogen atom, x and / or y is preferably 0, and x and y are more preferably 0.
[0113] In addition, in formula (1), from the viewpoint of improving the adhesion between the asphalt composition and the aggregate, each R' is preferably an alkoxy group having 1 to 12 carbon atoms (e.g., methoxy, ethoxy, butoxy), more preferably an alkoxy group having 1 to 5 carbon atoms, and even more preferably an alkoxy group having 1 to 3 carbon atoms.
[0114] As the silane, from the viewpoint of improving the adhesion between the asphalt composition and the aggregate, at least one selected from vinyltrimethoxysilane, vinyltriethoxysilane, and 3-(trimethoxysilyl)propyl methacrylate is preferred.
[0115] From the viewpoint of improving the adhesion between the asphalt composition and the aggregate, the petroleum resin (A) is preferably hydrogenated (hydrogenated) to form a hydrogenated product. The hydrogenated product of the petroleum resin (A) may be a partially hydrogenated type in which the petroleum resin (A) is partially hydrogenated, or a fully hydrogenated type in which the petroleum resin (A) is fully hydrogenated.
[0116] It should be noted that the petroleum resin (A) can be in the form of a copolymer as described above, but the structural difference is as follows when compared with Patent Document 1 which can be in the form of a modified product.
[0117] In modified products, free radicals attack the petroleum resin, adding silanes to the decomposed sites. This results in the modified sites becoming low molecular weight, with Si adhering to the low molecular weight side. On the other hand, copolymers have monomers with roughly the same degree of copolymerizability, so Si is uniformly adhering.
[0118] That is, in the case of copolymers, Si is uniformly attached, so even if the content is high, no localized Si sites are generated. As a result, high Si content can be achieved without gelation. On the other hand, in the case of modified products, Si is unevenly attached, so there are parts with high Si concentrations in the molecules (localized Si sites are generated), which reduces the proportion of Si that effectively functions with the hydroxyl groups on the aggregate surface, increases the probability of the presence of molecules without Si, and reduces the effect of improving water resistance.
[0119] Therefore, the copolymer form can be expected to exhibit a higher effect of improving water resistance when used as an asphalt composite material, from the viewpoint of being able to increase the Si content compared to the modified form.
[0120] <Method for producing petroleum resin (A)>
[0121] The method for producing petroleum resin (A) is not particularly limited. For example, it is preferred that the monomers, silanes and polymerization solvent are supplied to a polymerization reaction tank, and the monomers and silanes are copolymerized under specified conditions to produce petroleum resin (A).
[0122] The amount of the silane used is preferably 0.1 to 80 parts by mass, more preferably 0.5 to 50 parts by mass, further preferably 1 to 30 parts by mass, and even more preferably 5 to 28 parts by mass, based on 100 parts by mass of the monomers.
[0123] Here, representative examples of the polymerization solvent include aromatic solvents, cycloalkane solvents, aliphatic hydrocarbon solvents, etc. Specific examples of the polymerization solvent include toluene, xylene, cyclohexane, methylcyclohexane, dimethylcyclohexane, and ethylcyclohexane.
[0124] The amount of the polymerization solvent used is preferably 10 to 300 parts by mass, more preferably 20 to 200 parts by mass, and even more preferably 30 to 100 parts by mass, relative to 100 parts by mass of the monomers.
[0125] The conditions for the copolymerization reaction are not particularly limited, but the reaction temperature is preferably 150 to 350°C, more preferably 200 to 350°C, and even more preferably 230 to 300°C; the reaction pressure is preferably 0 to 5 MPaG, more preferably 0 to 3 MPaG, and even more preferably 0.1 to 2 MPaG; and the reaction time is preferably 1 to 10 hours, more preferably 1 to 8 hours, and even more preferably 1 to 5 hours. It should be noted that the "G" in "MPaG" represents gauge pressure.
[0126] In addition, the method for converting the petroleum resin (A) into a hydrogenate is not particularly limited. For example, it is preferred that the petroleum resin (A) is dissolved in a hydrogenation solvent in a hydrogenation reaction tank, and hydrogen is added under prescribed conditions in the presence of a hydrogenation reaction catalyst as needed to cause a hydrogenation reaction to occur, thereby generating a hydrogenate of the petroleum resin (A).
[0127] Here, examples of the hydrogenation solvent include cyclohexane, methylcyclohexane, dimethylcyclohexane, ethylcyclohexane, and tetrahydrofuran.
[0128] The amount of the hydrogenated solvent used is preferably 30 to 300 parts by mass, more preferably 50 to 250 parts by mass, and even more preferably 70 to 150 parts by mass, based on 100 parts by mass of the petroleum resin (A).
[0129] Examples of the hydrogenation reaction catalyst include catalysts containing at least one metal component selected from nickel, palladium, cobalt, platinum, and rhodium.
[0130] The prescribed conditions for the hydrogenation reaction are not particularly limited, but the reaction temperature is preferably 100 to 300° C., more preferably 150 to 280° C., and even more preferably 180 to 250° C. The hydrogen supply pressure is preferably 0.5 to 10 MPaG, more preferably 1 to 8 MPaG, and even more preferably 2 to 7 MPaG. The reaction time is preferably 1 to 20 hours, more preferably 2 to 15 hours, and even more preferably 3 to 10 hours.
[0131] As described above, the petroleum resin (A) can be in the form of a copolymer. However, when compared with Patent Document 1 in which the petroleum resin (A) can be in the form of a modified product, the differences in production process are as follows.
[0132] Regarding copolymers, unlike modified products, the production of petroleum resins does not require a silane modification step using silanes, and thus the production process can be simplified, leading to the expected economic advantage.
[0133] <Straight-run asphalt>
[0134] The asphalt composition contains a petroleum resin (A) and straight-run asphalt.
[0135] Straight-run asphalt can be used as asphalt base oil.
[0136] As the straight-run asphalt, the asphalt specified in JIS K2207: Table 3 or a mixture thereof can be used.
[0137] The needle penetration of straight-run asphalt is preferably 30-100, more preferably 40-90, and even more preferably 50-80.
[0138] It should be noted that the needle penetration can be measured according to JIS K2207:6.3 Penetration test method.
[0139] <Asphalt Composition>
[0140] The asphalt composition contains a petroleum resin (A) and straight-run asphalt.
[0141] From the viewpoint of improving the adhesion between the asphalt composition and the aggregate, the content of the petroleum resin (A) in the asphalt composition is preferably from 0.1% by mass to 5% by mass, more preferably from 0.1% by mass to 3% by mass, further preferably from 0.15% by mass to 3% by mass, and even more preferably from 0.3% by mass to 3% by mass.
[0142] From the viewpoint of improving the adhesion between the asphalt composition and the aggregate, the content of the straight-run asphalt in the asphalt composition is preferably 70.00 to 99.99% by mass, more preferably 90 to 99.90% by mass, and even more preferably 93 to 99.90% by mass.
[0143] In addition to the petroleum resin (A) and straight-run asphalt, the asphalt composition may contain various additives within a range that does not impair the effects of the present invention. Examples of such additives include antioxidants, adhesion promoters, emulsifiers, chemical modifiers, fibers, pigments, rubber-based additives, tackifiers, and regeneration additives.
[0144] When the additive is used, the content thereof in the asphalt composition is preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, and even more preferably 3% by mass or less.
[0145] <Method for producing asphalt composition>
[0146] The method for producing the asphalt composition is not particularly limited. For example, it is preferred that: after the petroleum resin (A) is crushed to a diameter below a specified diameter, the crushed petroleum resin (A) and straight-run asphalt are added to a stainless steel container in a specified ratio, and heated, stirred and mixed under specified conditions to produce the asphalt composition.
[0147] Before stirring and mixing the petroleum resin (A) and the straight-run asphalt, the petroleum resin (A) is crushed to a diameter of preferably 10 mm or less, more preferably 7 mm or less, and even more preferably 5 mm or less, thereby shortening the stirring and mixing time.
[0148] The prescribed conditions for stirring and mixing are not particularly limited, but the heating condition is preferably 80° C. or higher, more preferably 100° C. or higher, and further preferably 150° C. or higher. The stirring condition is preferably 500 to 8000 rpm, preferably 700 to 7000 rpm, and further preferably 1000 to 5000 rpm. The stirring and mixing time is preferably 3 to 60 minutes, more preferably 5 to 45 minutes, and further preferably 10 to 30 minutes.
[0149] <Asphalt composite materials>
[0150] The asphalt composite material as one embodiment of the first invention contains the asphalt composition of the first invention and aggregate, and the content of the asphalt composition is preferably 0.1 to 30 mass%, more preferably 1 to 20 mass%, more preferably 1 to 15 mass%, further preferably 1 to 10 mass%, and even more preferably 2 to 7 mass%.
[0151] Asphalt composite materials with desired properties can be obtained by adding aggregates having a predetermined particle size to an asphalt composition and mixing them at a predetermined rotational speed. The temperature when mixing the asphalt composition and the aggregates is preferably about 150 to 200°C.
[0152] [Second invention: Petroleum resin (B)]
[0153] Hereinafter, the petroleum resin (B) according to the second invention will be described.
[0154] A petroleum resin (B) is obtained by copolymerizing monomers containing at least one cyclic olefin having an ethylenically unsaturated group selected from the group consisting of a C5 fraction, a C8 fraction, a C9 fraction obtained by decomposing naphtha, and dicyclopentadiene, and silanes.
[0155] The petroleum resin (B) satisfies the following (b1) and (b2).
[0156] (b1) containing 0.1% by mass or more and 10% by mass or less of silicon element in terms of silicon atoms;
[0157] (b2) The weight average molecular weight (Mw) is 500 or more and 3,000 or less.
[0158] It should be noted that the above-mentioned physical properties of the petroleum resin (B) can be appropriately adjusted by the selection of raw material monomers, polymerization solvent and catalyst, their amounts, polymerization temperature, reaction pressure and other polymerization conditions.
[0159] The second invention provides a petroleum resin (B) that, when added to asphalt, improves the water resistance of an asphalt composite (a mixture of asphalt and aggregate) and thus extends the life of asphalt roads. The reason for this is not necessarily certain, but it is considered as follows.
[0160] Typically, when it comes to asphalt roads, if moisture is present at the interface between the aggregate and asphalt, the hydroxyl groups on the aggregate surface have a higher affinity for moisture than the aggregate surface for asphalt. This causes asphalt to peel from the aggregate surface, potentially damaging the asphalt road if subjected to loads such as from vehicles. In contrast, adding petroleum resin (B) to asphalt causes the hydroxyl groups on the aggregate surface to react with the silane-containing groups in the petroleum resin (B), chemically bonding the aggregate and the petroleum resin (B). This improves the affinity between the aggregate and asphalt, and thus enhances the adhesion between the aggregate and asphalt. It is believed that even if moisture is present near the aggregate surface, the aggregate and petroleum resin (B) remain connected due to chemical bonding, preventing peeling and maintaining the adhesion between the aggregate and asphalt. This improves the water resistance and durability of the asphalt road.
[0161] It should be noted that the above-mentioned mechanism related to the effects of the present invention is speculation, but the present invention is not limited thereto.
[0162] The petroleum resin (B) contains silicon element in an amount of 0.1% by mass to 10% by mass, preferably 0.3% by mass or more, more preferably 0.4% by mass or more, and even more preferably 0.5% by mass or more, calculated as silicon atoms. Furthermore, the amount is preferably less than 3.1% by mass, more preferably less than 1.7% by mass, and even more preferably 1.0% by mass or less. The silicon element is preferably derived from an organosilane structure.
[0163] If the silicon element concentration of the petroleum resin (B) is below the above range (less than 0.1% by mass), it may be difficult to react with the aggregate surface, and the water resistance of the asphalt composite material may become insufficient.
[0164] On the other hand, if the silicon concentration of the petroleum resin (B) exceeds the above range (exceeds 10% by mass), the petroleum resins (B) may react with each other, increase their molecular weight, reduce their miscibility with asphalt, and fail to improve the water resistance of the asphalt composite material.
[0165] It should be noted that the silicon element concentration can be measured by ICP emission spectrometry, and specifically, can be determined by the method described in the Examples.
[0166] It should be noted that when a petroleum resin (B) is used as an asphalt composition, if the silicon concentration of the petroleum resin (B) exceeds 1.0% by mass, the petroleum resin (B) may cross-link with each other due to exposure to high temperatures in the presence of water or in the presence of acids or alkalis, resulting in a possibility of reducing the effect of improving water resistance.
[0167] The weight average molecular weight (Mw) of the petroleum resin (B) is 500 or more and 3,000 or less, preferably 700 or more, more preferably 1,000 or more, further preferably 1,200 or more, further preferably 1,500 or more, and preferably 3,000 or less, more preferably 2,800 or less, further preferably 2,500 or less.
[0168] When the weight average molecular weight (Mw) of the petroleum resin (B) is smaller than the above range (less than 500), the hardness at room temperature may be insufficient or the resin may become brittle, resulting in reduced strength and decreased durability as an asphalt road.
[0169] On the other hand, if the weight average molecular weight (Mw) of the petroleum resin (B) exceeds the above range (exceeds 3,000), the viscosity may increase when mixed with asphalt at high temperature, thereby deteriorating miscibility with asphalt and failing to exhibit sufficient water resistance.
[0170] From the viewpoint of improving the adhesion between aggregate and asphalt, the molecular weight distribution (Mw / Mn) of the petroleum resin (B) is preferably 5.0 or less, more preferably 4.0 or less, and even more preferably 3.0 or less.
[0171] The weight average molecular weight (Mw) and the number average molecular weight (Mn) are both polystyrene-equivalent molecular weights and can be measured by gel permeation chromatography (GPC). Specifically, they can be determined by the method described in Examples.
[0172] The petroleum resin (B) preferably satisfies the following (b3).
[0173] (b3) The softening point is 70 to 150°C.
[0174] From the viewpoint of improving the adhesion between the aggregate and the asphalt, the softening point of the petroleum resin (B) is preferably 70 to 150°C, more preferably 80 to 140°C, and even more preferably 90 to 140°C.
[0175] In addition, the softening point can be measured according to JIS K 6863:1994.
[0176] The petroleum resin (B) preferably satisfies the following (b4).
[0177] (b4) The bromine value is 0.5 to 30 g / 100 g.
[0178] From the viewpoint of improving the adhesion between aggregate and asphalt, the bromine value of the petroleum resin (B) is preferably 0.5 to 30 g / 100 g, more preferably 1.0 to 25 g / 100 g, and even more preferably 2.0 to 20 g / 100 g.
[0179] In addition, the bromine value can be measured according to JIS K 2605:1996.
[0180] The petroleum resin (B) contains repeating units derived from monomers and repeating units derived from silanes, and is preferably obtained by copolymerizing monomers and silanes.
[0181] (Single type)
[0182] The monomers constituting the petroleum resin (B) include at least one cyclic olefin having an ethylenically unsaturated group selected from the C5 fraction, C8 fraction, and C9 fraction obtained by decomposing naphtha and cyclopentadiene compounds, preferably cyclopentadiene compounds, and more preferably dicyclopentadiene.
[0183] Furthermore, as monomers, it is preferable to use a cyclopentadiene compound as a first raw material and a vinyl aromatic compound as a second raw material. The first raw material may be used alone without using the second raw material.
[0184] Examples of the cyclopentadiene-based compound include cyclopentadiene, methylcyclopentadiene, ethylcyclopentadiene, and dimers and co-dimers thereof. Among these, dicyclopentadiene is preferred as the cyclopentadiene-based compound.
[0185] Examples of the vinyl aromatic compound include styrene, α-methylstyrene, β-methylstyrene, vinyltoluene, vinylxylene, indene, methylindene, and ethylindene. Among these, styrene is preferred as the vinyl aromatic compound.
[0186] The mixing ratio of the cyclopentadiene compound and the vinyl aromatic compound is not particularly limited, but is preferably cyclopentadiene compound:vinyl aromatic compound=80:20 to 20:80, more preferably 75:25 to 25:75, in terms of mass ratio.
[0187] (Silanes)
[0188] The silanes constituting the petroleum resin (B) are not particularly limited, but preferably have a structure represented by the following formula (1).
[0189] Formula (1):
[0190] CH2=CR-(COO) x (C n H2n ) y SiR'3
[0191] (In formula (1), R is a hydrogen atom or a methyl group; x and y are 0 or 1, wherein when x is 1, y is 1; n is an integer from 1 to 12, preferably from 1 to 4; each R' is independently an alkoxy group having 1 to 12 carbon atoms (e.g., methoxy, ethoxy, butoxy), an aryloxy group (e.g., phenoxy), an aralkyloxy group (e.g., benzyloxy), an aliphatic acyloxy group having 1 to 12 carbon atoms (e.g., formyloxy, acetoxy, propionyloxy), an amino group or a substituted amino group (alkylamino, arylamino), or a lower alkyl group having 1 to 6 carbon atoms, wherein two or less of the three R' groups are alkyl groups.)
[0192] In formula (1), from the viewpoint of improving the adhesion between the asphalt composition and the aggregate, R is preferably a hydrogen atom, x and / or y is preferably 0, and x and y are more preferably 0.
[0193] In addition, in formula (1), from the viewpoint of improving the adhesion between the asphalt composition and the aggregate, each R' is preferably an alkoxy group having 1 to 12 carbon atoms (e.g., methoxy, ethoxy, butoxy), more preferably an alkoxy group having 1 to 5 carbon atoms, and even more preferably an alkoxy group having 1 to 3 carbon atoms.
[0194] As the silane, from the viewpoint of improving the adhesion between the asphalt composition and the aggregate, at least one selected from vinyltrimethoxysilane, vinyltriethoxysilane, and 3-(trimethoxysilyl)propyl methacrylate is preferred.
[0195] From the viewpoint of improving the adhesion between the asphalt composition and the aggregate, the petroleum resin (B) is preferably hydrogenated (hydrogenated) to form a hydrogenated product. The hydrogenated product of the petroleum resin (B) may be a partially hydrogenated type in which the petroleum resin (B) is partially hydrogenated, or a fully hydrogenated type in which the petroleum resin (B) is fully hydrogenated.
[0196] It should be noted that the petroleum resin (B) can be in the form of a copolymer as described above, but the structural difference is as follows when compared with Patent Document 1 which can be in the form of a modified product.
[0197] In modified products, free radicals attack the petroleum resin, adding silanes to the decomposed sites. This results in the modified sites becoming low molecular weight, with Si adhering to the low molecular weight side. On the other hand, copolymers have monomers with roughly the same degree of copolymerizability, so Si is uniformly adhering.
[0198] That is, in the case of copolymers, Si is uniformly attached, so even if the content is high, no localized Si sites are generated. As a result, high Si content can be achieved without gelation. On the other hand, in the case of modified products, Si is unevenly attached, so there are parts with high Si concentrations in the molecules (localized Si sites are generated), which reduces the proportion of Si that effectively functions with the hydroxyl groups on the aggregate surface, increases the probability of the presence of molecules without Si, and reduces the effect of improving water resistance.
[0199] Therefore, the copolymer form can be expected to exhibit a higher effect of improving water resistance when used as an asphalt composite material, from the viewpoint of being able to increase the Si content compared to the modified form.
[0200] <Method for producing petroleum resin (B)>
[0201] The method for producing petroleum resin (B) is not particularly limited. For example, it is preferred that the monomers, silanes and polymerization solvent are supplied to a polymerization reaction tank, and the monomers and silanes are copolymerized under specified conditions to produce petroleum resin (B).
[0202] The amount of the silane used is preferably 0.1 to 80 parts by mass, more preferably 0.5 to 50 parts by mass, and even more preferably 1 to 30 parts by mass, relative to 100 parts by mass of the monomers.
[0203] Here, representative examples of the polymerization solvent include aromatic solvents, cycloalkane solvents, aliphatic hydrocarbon solvents, etc. Specific examples of the polymerization solvent include toluene, xylene, cyclohexane, methylcyclohexane, dimethylcyclohexane, and ethylcyclohexane.
[0204] The amount of the polymerization solvent used is preferably 10 to 300 parts by mass, more preferably 20 to 200 parts by mass, and even more preferably 30 to 100 parts by mass, relative to 100 parts by mass of the monomers.
[0205] The conditions for the copolymerization reaction are not particularly limited, but the reaction temperature is preferably 150 to 350°C, more preferably 200 to 350°C, and even more preferably 230 to 300°C; the reaction pressure is preferably 0 to 5 MPaG, more preferably 0 to 3 MPaG, and even more preferably 0.1 to 2 MPaG; and the reaction time is preferably 1 to 10 hours, more preferably 1 to 8 hours, and even more preferably 1 to 5 hours. It should be noted that the "G" in "MPaG" represents gauge pressure.
[0206] In addition, the method for converting the petroleum resin (B) into a hydrogenated product is not particularly limited. For example, it is preferred that the petroleum resin (B) is dissolved in a hydrogenation solvent in a hydrogenation reaction tank, and hydrogen is added under prescribed conditions in the presence of a hydrogenation reaction catalyst as needed to cause a hydrogenation reaction to occur, thereby generating a hydrogenated product of the petroleum resin (B).
[0207] Here, examples of the hydrogenation solvent include cyclohexane, methylcyclohexane, dimethylcyclohexane, ethylcyclohexane, and tetrahydrofuran.
[0208] The amount of the hydrogenated solvent used is preferably 30 to 300 parts by mass, more preferably 50 to 250 parts by mass, and even more preferably 70 to 150 parts by mass, based on 100 parts by mass of the petroleum resin (B).
[0209] Examples of the hydrogenation reaction catalyst include catalysts containing at least one metal component selected from nickel, palladium, cobalt, platinum, and rhodium.
[0210] The prescribed conditions for the hydrogenation reaction are not particularly limited, but the reaction temperature is preferably 100 to 300° C., more preferably 150 to 280° C., and even more preferably 180 to 250° C. The hydrogen supply pressure is preferably 0.5 to 10 MPaG, more preferably 1 to 8 MPaG, and even more preferably 2 to 7 MPaG. The reaction time is preferably 1 to 20 hours, more preferably 2 to 15 hours, and even more preferably 3 to 10 hours.
[0211] As described above, the petroleum resin (B) can be in the form of a copolymer. However, when compared with Patent Document 1 in which the petroleum resin (B) can be in the form of a modified product, the differences in production process are as follows.
[0212] Regarding copolymers, unlike modified products, the production of petroleum resins does not require a silane modification step using silanes, and thus the production process can be simplified, leading to the expected economic advantage.
[0213] <Straight-run asphalt>
[0214] The petroleum resin (B) can be used by being contained in an asphalt composition.
[0215] When the asphalt composition contains the petroleum resin (B) and straight-run asphalt, the straight-run asphalt can be used as the asphalt base oil.
[0216] As the straight-run asphalt, the asphalt specified in JIS K2207: Table 3 or a mixture thereof can be used.
[0217] The needle penetration of straight-run asphalt is preferably 30-100, more preferably 40-90, and even more preferably 50-80.
[0218] It should be noted that the needle penetration can be measured according to JIS K2207:6.3 Penetration test method.
[0219] <Asphalt Composition>
[0220] When the asphalt composition contains a petroleum resin (B) and straight-run asphalt, from the viewpoint of improving the adhesion between the asphalt composition and the aggregate, the content of the petroleum resin (B) in the asphalt composition is preferably from 0.1% by mass to 5% by mass, more preferably from 0.1% by mass to 3% by mass, further preferably from 0.15% by mass to 3% by mass, and even more preferably from 0.3% by mass to 3% by mass.
[0221] From the viewpoint of improving the adhesion between the asphalt composition and the aggregate, the content of the straight-run asphalt in the asphalt composition is preferably 70.00 to 99.99% by mass, more preferably 90 to 99.90% by mass, and even more preferably 93 to 99.90% by mass.
[0222] In addition to the petroleum resin (B) and straight-run asphalt, the asphalt composition may contain various additives within a range that does not impair the effects of the present invention. Examples of additives include antioxidants, adhesion promoters, emulsifiers, chemical modifiers, fibers, pigments, rubber-based additives, tackifiers, and regeneration additives.
[0223] When the additive is used, the content thereof in the asphalt composition is preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, and even more preferably 3% by mass or less.
[0224] <Method for producing asphalt composition>
[0225] The method for producing the asphalt composition is not particularly limited. For example, it is preferred that: after the petroleum resin (B) is crushed to a diameter below a specified diameter, the crushed petroleum resin (B) and straight-run asphalt are added to a stainless steel container in a specified ratio, and heated, stirred and mixed under specified conditions to produce the asphalt composition.
[0226] Before stirring and mixing the petroleum resin (B) and the straight-run asphalt, the petroleum resin (B) is crushed to a diameter of preferably 10 mm or less, more preferably 7 mm or less, and even more preferably 5 mm or less, thereby shortening the stirring and mixing time.
[0227] The prescribed conditions for stirring and mixing are not particularly limited, but the heating condition is preferably 80° C. or higher, more preferably 100° C. or higher, and further preferably 150° C. or higher. The stirring condition is preferably 500 to 8000 rpm, preferably 700 to 7000 rpm, and further preferably 1000 to 5000 rpm. The stirring and mixing time is preferably 3 to 60 minutes, more preferably 5 to 45 minutes, and further preferably 10 to 30 minutes.
[0228] <Asphalt composite materials>
[0229] The asphalt composite material as one embodiment of the second invention comprises an asphalt composition containing the petroleum resin (B) of the second invention and aggregate, wherein the content of the asphalt composition is preferably 0.1 to 30 mass%, more preferably 1 to 20 mass%, more preferably 1 to 15 mass%, further preferably 1 to 10 mass%, and even more preferably 2 to 7 mass%.
[0230] Asphalt composite materials with desired properties can be obtained by adding aggregates having a predetermined particle size to an asphalt composition and mixing them at a predetermined rotational speed. The temperature when mixing the asphalt composition and the aggregates is preferably about 150 to 200°C.
[0231] [Third Invention: Hydrogenated Petroleum Resin (C)]
[0232] Hereinafter, the hydrogenated petroleum resin (C) according to the third invention will be described.
[0233] A hydrogenated petroleum resin (C) obtained by copolymerizing monomers containing at least one cyclic olefin having an ethylenically unsaturated group selected from the group consisting of a C5 fraction, a C8 fraction, and a C9 fraction obtained by decomposing naphtha and a cyclopentadiene-based compound, and silanes.
[0234] The hydrogenated petroleum resin (C) satisfies the following (c1) and (c2).
[0235] (c1) containing 0.1% by mass or more and 10% by mass or less of silicon element in terms of silicon atoms;
[0236] (c2) The weight average molecular weight (Mw) is 500 or more and 3,000 or less.
[0237] It should be noted that the above-mentioned physical properties of the hydrogenated petroleum resin (C) can be appropriately adjusted by the selection of raw material monomers, polymerization solvents, and catalysts, their amounts, polymerization temperature, reaction pressure, and other polymerization conditions.
[0238] The third invention provides a hydrogenated petroleum resin (C) that, when added to asphalt, improves the water resistance of an asphalt composite (a mixture of asphalt and aggregate) and thus extends the life of asphalt roads. The reason for this is not necessarily certain, but it is considered as follows.
[0239] Typically, in asphalt roads, if moisture is present at the interface between the aggregate and asphalt, the hydroxyl groups on the aggregate surface have a higher affinity for moisture than the aggregate surface's affinity for asphalt. Consequently, asphalt peels off from the aggregate surface, potentially damaging the road if subjected to a load such as a car. In contrast, if hydrogenated petroleum resin (C) is added to asphalt, the hydroxyl groups on the aggregate surface react with the silane-containing groups in the hydrogenated petroleum resin (C), chemically bonding the aggregate and the hydrogenated petroleum resin (C). This improves the affinity between the aggregate and asphalt, improving the adhesion between the aggregate and asphalt. It can be assumed that even if moisture is present near the aggregate surface, the aggregate and hydrogenated petroleum resin (C) remain connected due to chemical bonding, preventing peeling. This maintains the adhesion between the aggregate and asphalt, improving the water resistance and durability of the asphalt road.
[0240] It should be noted that the above-mentioned mechanism related to the effects of the present invention is speculation, but the present invention is not limited thereto.
[0241] The hydrogenated petroleum resin (C) contains silicon in an amount of 0.1% by mass or more and 10% by mass or less, preferably 0.3% by mass or more, more preferably 0.4% by mass or more, and further preferably 0.5% by mass or more, and preferably 3.1% by mass or less, more preferably 1.7% by mass or less, and further preferably 1.0% by mass or less, calculated as silicon atoms. The silicon is preferably derived from an organosilane structure.
[0242] If the silicon element concentration of the hydrogenated petroleum resin (C) is lower than the above range (less than 0.1% by mass), it may be difficult to react with the aggregate surface, and the water resistance of the asphalt composite material may become insufficient.
[0243] On the other hand, if the silicon element concentration of the above-mentioned hydrogenated petroleum resin (C) exceeds the above-mentioned range (exceeding 10% by mass), the above-mentioned hydrogenated petroleum resins (C) may react with each other, the molecular weight may increase, the miscibility with asphalt may decrease, and the water resistance of the asphalt composite material may not be improved.
[0244] It should be noted that the silicon element concentration can be measured by ICP emission spectrometry, and specifically, can be determined by the method described in the Examples.
[0245] It should be noted that when a hydrogenated petroleum resin (C) is used as an asphalt composition, if the silicon concentration of the above-mentioned hydrogenated petroleum resin (C) exceeds 1.0% by mass, the hydrogenated petroleum resin (C) may be cross-linked with each other due to exposure to high temperatures in the presence of water or in the presence of acids or alkalis, resulting in a possibility that the effect of improving water resistance will be reduced.
[0246] The weight average molecular weight (Mw) of the hydrogenated petroleum resin (C) is 500 or more and 3,000 or less, preferably 700 or more, more preferably 1,000 or more, further preferably 1,200 or more, further preferably 1,500 or more, and preferably 3,000 or less, more preferably 2,800 or less, further preferably 2,500 or less.
[0247] When the weight average molecular weight (Mw) of the hydrogenated petroleum resin (C) is smaller than the above range (less than 500), the hardness at room temperature may be insufficient or the resin may become brittle, resulting in reduced strength and decreased durability as an asphalt road.
[0248] On the other hand, if the weight average molecular weight (Mw) of the hydrogenated petroleum resin (C) exceeds the above range (exceeds 3,000), the viscosity may increase when mixed with asphalt at high temperature, thereby deteriorating the miscibility with asphalt and failing to exhibit sufficient water resistance.
[0249] From the viewpoint of improving the adhesion between aggregate and asphalt, the molecular weight distribution (Mw / Mn) of the hydrogenated petroleum resin (C) is preferably 5.0 or less, more preferably 4.0 or less, and even more preferably 3.0 or less.
[0250] The weight average molecular weight (Mw) and the number average molecular weight (Mn) are both polystyrene-equivalent molecular weights and can be measured by gel permeation chromatography (GPC). Specifically, they can be determined by the method described in Examples.
[0251] The hydrogenated petroleum resin (C) preferably satisfies the following (c3).
[0252] (c3) The softening point is 70 to 150°C.
[0253] The softening point of the hydrogenated petroleum resin (C) is preferably 70 to 150°C, more preferably 80 to 140°C, and even more preferably 90 to 140°C from the viewpoint of improving the adhesion between the aggregate and the asphalt.
[0254] In addition, the softening point can be measured according to JIS K 6863:1994.
[0255] The hydrogenated petroleum resin (C) preferably satisfies the following (c4).
[0256] (c4) The bromine value is 0.5 to 30 g / 100 g.
[0257] From the viewpoint of improving the adhesion between aggregate and asphalt, the bromine value of the hydrogenated petroleum resin (C) is preferably 0.5 to 30 g / 100 g, more preferably 1.0 to 25 g / 100 g, and even more preferably 2.0 to 20 g / 100 g.
[0258] In addition, the bromine value can be measured according to JIS K 2605:1996.
[0259] The hydrogenated petroleum resin (C) comprises repeating units derived from monomers and repeating units derived from silanes, and is preferably obtained by copolymerizing monomers and silanes.
[0260] (Single type)
[0261] The monomers constituting the hydrogenated petroleum resin (C) include at least one cyclic olefin having an ethylenically unsaturated group selected from the C5 fraction, C8 fraction, C9 fraction obtained by decomposing naphtha and cyclopentadiene compounds, preferably cyclopentadiene compounds, more preferably dicyclopentadiene.
[0262] Furthermore, as monomers, it is preferable to use a cyclopentadiene compound as a first raw material and a vinyl aromatic compound as a second raw material. The first raw material may be used alone without using the second raw material.
[0263] Examples of the cyclopentadiene-based compound include cyclopentadiene, methylcyclopentadiene, ethylcyclopentadiene, and dimers and co-dimers thereof. Among these, dicyclopentadiene is preferred as the cyclopentadiene-based compound.
[0264] Examples of the vinyl aromatic compound include styrene, α-methylstyrene, β-methylstyrene, vinyltoluene, vinylxylene, indene, methylindene, and ethylindene. Among these, styrene is preferred as the vinyl aromatic compound.
[0265] The mixing ratio of the cyclopentadiene compound and the vinyl aromatic compound is not particularly limited, but is preferably cyclopentadiene compound:vinyl aromatic compound=80:20 to 20:80, more preferably 75:25 to 25:75, in terms of mass ratio.
[0266] (Silanes)
[0267] The silanes constituting the hydrogenated petroleum resin (C) are not particularly limited, but preferably have a structure represented by the following formula (1).
[0268] Formula (1):
[0269] CH2=CR-(COO)x (C n H 2n ) y SiR'3
[0270] (In formula (1), R is a hydrogen atom or a methyl group; x and y are 0 or 1, wherein when x is 1, y is 1; n is an integer from 1 to 12, preferably from 1 to 4; each R' is independently an alkoxy group having 1 to 12 carbon atoms (e.g., methoxy, ethoxy, butoxy), an aryloxy group (e.g., phenoxy), an aralkyloxy group (e.g., benzyloxy), an aliphatic acyloxy group having 1 to 12 carbon atoms (e.g., formyloxy, acetoxy, propionyloxy), an amino group or a substituted amino group (alkylamino, arylamino), or a lower alkyl group having 1 to 6 carbon atoms, wherein two or less of the three R' groups are alkyl groups.)
[0271] In formula (1), from the viewpoint of improving the adhesion between the asphalt composition and the aggregate, R is preferably a hydrogen atom, x and / or y is preferably 0, and x and y are more preferably 0.
[0272] In addition, in formula (1), from the viewpoint of improving the adhesion between the asphalt composition and the aggregate, each R' is preferably an alkoxy group having 1 to 12 carbon atoms (e.g., methoxy, ethoxy, butoxy), more preferably an alkoxy group having 1 to 5 carbon atoms, and even more preferably an alkoxy group having 1 to 3 carbon atoms.
[0273] As the silane, from the viewpoint of improving the adhesion between the asphalt composition and the aggregate, at least one selected from vinyltrimethoxysilane, vinyltriethoxysilane, and 3-(trimethoxysilyl)propyl methacrylate is preferred.
[0274] It should be noted that the hydrogenated petroleum resin (C) can be in the form of a copolymer as described above, but the structural difference is as follows when compared with Patent Document 1 which can be in the form of a modified product.
[0275] Regarding the modified product, since free radicals attack the hydrogenated petroleum resin, silanes are added to the decomposed sites, so the modified sites become low molecular weight and Si is attached to the low molecular weight side. On the other hand, the copolymer is made of monomers with roughly the same degree of copolymerizability, so Si is evenly attached.
[0276] That is, in the case of copolymers, Si is uniformly attached, so even if the content is high, no localized Si sites are generated. As a result, high Si content can be achieved without gelation. On the other hand, in the case of modified products, Si is unevenly attached, so there are parts with high Si concentrations in the molecules (localized Si sites are generated), which reduces the proportion of Si that effectively functions with the hydroxyl groups on the aggregate surface, increases the probability of the presence of molecules without Si, and reduces the effect of improving water resistance.
[0277] Therefore, the copolymer form can be expected to exhibit a higher effect of improving water resistance when used as an asphalt composite material, from the viewpoint of being able to increase the Si content compared to the modified form.
[0278] <Method for producing the petroleum resin constituting the hydrogenated petroleum resin (C)>
[0279] The method for manufacturing the petroleum resin constituting the hydrogenated petroleum resin (C) is not particularly limited. For example, it is preferred that the above-mentioned monomers, the above-mentioned silanes and the polymerization solvent are supplied to a polymerization reaction tank, and the above-mentioned monomers and the above-mentioned silanes are copolymerized under specified conditions to produce petroleum resin.
[0280] The amount of the silane used is preferably 0.1 to 80 parts by mass, more preferably 0.5 to 50 parts by mass, and even more preferably 1 to 30 parts by mass, relative to 100 parts by mass of the monomers.
[0281] Here, representative examples of the polymerization solvent include aromatic solvents, cycloalkane solvents, aliphatic hydrocarbon solvents, etc. Specific examples of the polymerization solvent include toluene, xylene, cyclohexane, methylcyclohexane, dimethylcyclohexane, and ethylcyclohexane.
[0282] The amount of the polymerization solvent used is preferably 10 to 300 parts by mass, more preferably 20 to 200 parts by mass, and even more preferably 30 to 100 parts by mass, relative to 100 parts by mass of the monomers.
[0283] The conditions for the copolymerization reaction are not particularly limited, but the reaction temperature is preferably 150 to 350°C, more preferably 200 to 350°C, and even more preferably 230 to 300°C; the reaction pressure is preferably 0 to 5 MPaG, more preferably 0 to 3 MPaG, and even more preferably 0.1 to 2 MPaG; and the reaction time is preferably 1 to 10 hours, more preferably 1 to 8 hours, and even more preferably 1 to 5 hours. It should be noted that the "G" in "MPaG" represents gauge pressure.
[0284] In addition, the method for hydrogenating petroleum resin to prepare hydrogenated petroleum resin (C) is not particularly limited. For example, it is preferred that the above-mentioned petroleum resin is dissolved in a hydrogenation solvent in a hydrogenation reaction tank, and hydrogen is added under prescribed conditions in the presence of a hydrogenation reaction catalyst as needed to cause a hydrogenation reaction to occur, thereby generating hydrogenated petroleum resin (C).
[0285] Here, examples of the hydrogenation solvent include cyclohexane, methylcyclohexane, dimethylcyclohexane, ethylcyclohexane, and tetrahydrofuran.
[0286] The amount of the hydrogenation solvent used is preferably 30 to 300 parts by mass, more preferably 50 to 250 parts by mass, and even more preferably 70 to 150 parts by mass, relative to 100 parts by mass of the petroleum resin.
[0287] Examples of the hydrogenation reaction catalyst include catalysts containing at least one metal component selected from nickel, palladium, cobalt, platinum, and rhodium.
[0288] The prescribed conditions for the hydrogenation reaction are not particularly limited, but the reaction temperature is preferably 100 to 300° C., more preferably 150 to 280° C., and even more preferably 180 to 250° C. The hydrogen supply pressure is preferably 0.5 to 10 MPaG, more preferably 1 to 8 MPaG, and even more preferably 2 to 7 MPaG. The reaction time is preferably 1 to 20 hours, more preferably 2 to 15 hours, and even more preferably 3 to 10 hours.
[0289] It should be noted that the hydrogenated petroleum resin (C) can be in the form of a copolymer as described above, but the difference in production process is as follows when compared with Patent Document 1 which can be in the form of a modified product.
[0290] Regarding copolymers, unlike modified products, the production of petroleum resins does not require a silane modification step using silanes, and thus the production process can be simplified, leading to the expected economic advantage.
[0291] <Straight-run asphalt>
[0292] The hydrogenated petroleum resin (C) can be used by being contained in the asphalt composition.
[0293] When the asphalt composition contains the hydrogenated petroleum resin (C) and straight-run asphalt, the straight-run asphalt can be used as the asphalt base oil.
[0294] As the straight-run asphalt, the asphalt specified in JIS K2207: Table 3 or a mixture thereof can be used.
[0295] The needle penetration of straight-run asphalt is preferably 30-100, more preferably 40-90, and even more preferably 50-80.
[0296] It should be noted that the needle penetration can be measured according to JIS K2207:6.3 Penetration test method.
[0297] <Asphalt Composition>
[0298] When the asphalt composition contains a hydrogenated petroleum resin (C) and a straight-run asphalt, from the viewpoint of improving the adhesion between the asphalt composition and the aggregate, the content of the hydrogenated petroleum resin (C) in the asphalt composition is preferably from 0.1% by mass to 5% by mass, more preferably from 0.1% by mass to 3% by mass, further preferably from 0.15% by mass to 3% by mass, and even more preferably from 0.3% by mass to 3% by mass.
[0299] From the viewpoint of improving the adhesion between the asphalt composition and the aggregate, the content of the straight-run asphalt in the asphalt composition is preferably 70.00 to 99.99% by mass, more preferably 90 to 99.90% by mass, and even more preferably 93 to 99.90% by mass.
[0300] In addition to the hydrogenated petroleum resin (C) and straight-run asphalt, the asphalt composition may contain various additives within a range that does not impair the effects of the present invention. Examples of such additives include antioxidants, adhesion promoters, emulsifiers, chemical modifiers, fibers, pigments, rubber-based additives, tackifiers, and regeneration additives.
[0301] When the additive is used, the content thereof in the asphalt composition is preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, and even more preferably 3% by mass or less.
[0302] <Method for producing asphalt composition>
[0303] The method for producing the asphalt composition is not particularly limited. For example, it is preferred that: after the hydrogenated petroleum resin (C) is crushed to a diameter below a specified diameter, the crushed hydrogenated petroleum resin (C) and straight-run asphalt are added to a stainless steel container in a specified ratio, and heated, stirred and mixed under specified conditions to produce the asphalt composition.
[0304] Before stirring and mixing the hydrogenated petroleum resin (C) and the straight-run asphalt, the stirring and mixing time can be shortened by pulverizing the hydrogenated petroleum resin (C) to a diameter of preferably 10 mm or less, more preferably 7 mm or less, and even more preferably 5 mm or less.
[0305] As the specified conditions in stirring and mixing, there are no particular limitations. The heating conditions are preferably 80 °C or higher, more preferably 100 °C or higher, and further preferably 150 °C or higher. The stirring conditions are preferably 500 to 8000 rpm, preferably 700 to 7000 rpm, and further preferably 1000 to 5000 rpm. The stirring and mixing time is preferably 3 to 60 minutes, more preferably 5 to 45 minutes, and further preferably 10 to 30 minutes.
[0306] <Asphalt composite material>
[0307] An asphalt composite material as a mode of the third invention includes an asphalt composition containing the hydrogenated petroleum resin (C) of the third invention and an aggregate. The content of the asphalt composition is preferably 0.1 to 30% by mass, more preferably 1 to 20% by mass, more preferably 1 to 15% by mass, further preferably 1 to 10% by mass, and even more preferably 2 to 7% by mass.
[0308] Regarding the asphalt composite material, by adding an aggregate having a specified particle size to the asphalt composition and mixing at a specified rotation speed, an asphalt composite material having a desired property can be obtained. The temperature during mixing the asphalt composition and the aggregate is preferably about 150 to 200 °C.
[0309] Examples
[0310] Next, the first invention, the second invention, and the third invention will be described in more detail by way of examples, but the first invention, the second invention, and the third invention are not at all limited to these examples. [[ID=I7]]
[0311] [Silicon element concentration] [[ID=I20]]
[0312] 0.1 g of the petroleum resin or hydrogenated petroleum resin produced in each example was heated in an electric furnace at 550 °C for 12 hours, and a measurement solution was prepared by alkali fusion of the ash. ICP emission spectroscopic analysis was performed using an ICP emission spectroscopic analyzer 720-ES (manufactured by Agilent Technologies, "720-ES") to determine the concentration of the silicon element.
[0313] [Weight-average molecular weight (Mw)]
[0314] Taking the petroleum resin or hydrogenated petroleum resin produced in each example as the object, the weight-average molecular weight (Mw) was determined by gel permeation chromatography (GPC). In the measurement, the following device and conditions were used to determine in terms of the molecular weight in terms of polystyrene conversion.
[0315] <GPC measurement device>
[0316] Equipment: "HLC8321GPC / HT" manufactured by Tosoh Corporation
[0317] Detector: RI detector
[0318] Column: 2 pieces of "TOSOH GMHHR-H(S)HT" manufactured by Tosoh Corporation
[0319] <Measurement Conditions>
[0320] Solvent: 1,2,4-trichlorobenzene
[0321] Measurement temperature: 145°C
[0322] Flow rate: 1.0 mL / min
[0323] Sample concentration: 0.5 mg / mL
[0324] Injection volume: 300 μL
[0325] Standard curve: Prepared using PS standard substances.
[0326] Molecular weight conversion: Calculated using the Universal Calibration method.
[0327] Analytical procedure: 8321GPC-WS
[0328] [Softening point]
[0329] The petroleum resin or hydrogenated petroleum resin produced in each example was used as an object and the measurement was performed in accordance with JIS K6863:1994.
[0330] [Bromine value]
[0331] The petroleum resin or hydrogenated petroleum resin produced in each example was used as an object and the measurement was performed in accordance with JIS K2605:1996.
[0332] [Evaluation of Asphalt Composition]
[0333] The hard sandstone aggregate of No. 6 crushed stone was washed with water and dried at 170°C for at least 1 hour. Next, 5.5g±0.5g of the asphalt composition was added to 100g±0.5g of the dried hard sandstone aggregate. The mixture was heated on a hot plate at 160-180°C while mixing and stirring for approximately 2-3 minutes to produce an asphalt composite material. Ten of these materials were selected. The selected asphalt composite materials were then added to 100mL of a 1.0mol / L aqueous sodium carbonate solution. The aqueous solution was then heated on a hot plate until it reached 90°C for 1 minute and cooled. The upper surface of the asphalt composite material was visually observed, and the area ratio of the asphalt covering the aggregate surface was calculated. Evaluation was performed according to the following criteria.
[0334] A: Peeling area ratio is less than 50%
[0335] B: The peeling area ratio is more than 50% and less than 70%
[0336] C: Peeling rate area exceeds 70%
[0337] Note that, here, the smaller the peeling area ratio of the upper surface of the asphalt composite material is, the more the peeling of the asphalt is suppressed, and the more excellent the water resistance of the asphalt composite material can be evaluated.
[0338] Comparative Preparation Example 1: Hydrogenated Petroleum Resin
[0339] 180 g of xylene was added to a 1-liter autoclave and the temperature was raised to 260° C. Subsequently, a mixture of 100 g of dicyclopentadiene and 100 g of styrene was added over 3 hours. The temperature was maintained for a further 75 minutes to allow polymerization to proceed, yielding a polymer mixture.
[0340] Thereafter, xylene was recovered from the obtained polymer mixture, and then low-boiling-point substances were distilled off by maintaining the pressure at 20 mmHg for 2 hours to obtain a petroleum resin.
[0341] 180 g of the obtained petroleum resin, 180 g of ethylcyclohexane, and 4 g of a nickel-based catalyst (N110 series) manufactured by JGC Catalysts & Chemicals Co., Ltd. were placed in a 1-liter autoclave. Hydrogen gas was introduced to a pressure of 5 MPa, and the temperature was raised from room temperature to 230°C. A hydrogenation reaction was then carried out for 8 hours while maintaining the hydrogen pressure at 5 MPa to obtain a hydrogenated petroleum resin.
[0342] Production Example 1: Petroleum resin (A1)
[0343] A 1-liter autoclave was charged with 180 g of xylene, 236 g of dicyclopentadiene, 108 g of styrene, and 72 g of vinyltrimethoxysilane (manufactured by Tokyo Chemical Industry Co., Ltd.). The internal pressure was adjusted to 0.15 MPa after nitrogen substitution. The temperature was raised to 278°C and maintained for 3 hours to allow polymerization to proceed, yielding a polymer mixture.
[0344] Thereafter, xylene was recovered from the obtained polymer mixture, and then low boiling point substances were distilled off by maintaining the pressure at 20 mmHg for 2 hours to obtain a petroleum resin (A1).
[0345] Production Example 2: Hydrogenated petroleum resin (A2)
[0346] 180 g of the petroleum resin obtained in Production Example 1, 180 g of ethylcyclohexane, and 8 g of a nickel-based catalyst (N110 series) manufactured by JGC Catalysts & Chemicals Co., Ltd. were placed in a 1-liter autoclave. Hydrogen gas was introduced to a pressure of 5 MPa, and the temperature was raised from room temperature to 230°C. A hydrogenation reaction was then carried out for 8 hours while maintaining the hydrogen pressure at 5 MPa to obtain a hydrogenated petroleum resin (A2).
[0347] Production Example 3: Petroleum resin (A3)
[0348] A 1-liter autoclave was charged with 180 g of xylene, 236 g of dicyclopentadiene, 108 g of styrene, and 11 g of vinyltrimethoxysilane (manufactured by Tokyo Chemical Industry Co., Ltd.). The internal pressure was adjusted to 0.15 MPa after nitrogen substitution. The temperature was raised to 278°C and maintained for 3 hours to allow polymerization to proceed, yielding a polymer mixture.
[0349] Thereafter, xylene was recovered from the obtained polymer mixture, and then low boiling point substances were distilled off by maintaining the pressure at 20 mmHg for 2 hours to obtain a petroleum resin (A3).
[0350] Production Example 4: Hydrogenated Petroleum Resin (A4)
[0351] 180 g of the petroleum resin (A3) obtained in Production Example 3, 180 g of ethylcyclohexane, and 8 g of a nickel-based catalyst (N110 series) manufactured by JGC Catalysts & Chemicals Co., Ltd. were placed in a 1-liter autoclave. Hydrogen gas was introduced to a pressure of 5 MPa, and the temperature was raised from room temperature to 230°C. A hydrogenation reaction was then carried out for 8 hours while maintaining the hydrogen pressure at 5 MPa to obtain a hydrogenated petroleum resin (A4).
[0352] [Manufacturing of Asphalt Composition]
[0353] Example 1
[0354] After the petroleum resin (A1) obtained in Preparation Example 1 was crushed to a diameter of less than 5 mm, the petroleum resin (A1) and straight-run asphalt (manufactured by Idemitsu Kosan Co., Ltd., with a needle penetration of 72) were added to a 200 mL stainless steel cylindrical container in a total amount of 50 g in the blending ratio shown in Table 1. The mixture was stirred and mixed for about 15 minutes at a temperature of not less than 160°C and a rotation speed of not less than 2,000 rpm and not more than 4,000 rpm using a stirring device and a mantle heater to obtain an asphalt composition.
[0355] Example 2
[0356] An asphalt composition was obtained in the same manner as in Example 1 except that the petroleum resin (A1) obtained in Production Example 1 was changed to the hydrogenated petroleum resin (A2) obtained in Production Example 2.
[0357] Example 3
[0358] An asphalt composition was obtained in the same manner as in Example 1 except that the petroleum resin (A1) obtained in Production Example 1 was changed to the petroleum resin (A3) obtained in Production Example 3.
[0359] Example 4
[0360] An asphalt composition was obtained in the same manner as in Example 1 except that the petroleum resin (A1) obtained in Production Example 1 was changed to the hydrogenated petroleum resin (A4) obtained in Production Example 4.
[0361] Comparative Example 1
[0362] An asphalt composition was obtained in the same manner as in Example 1 except that the petroleum resin (A1) obtained in Production Example 1 was changed to the hydrogenated petroleum resin obtained in Comparative Production Example 1 and the blending ratio was changed to that shown in Table 1.
[0363] Comparative Example 2
[0364] An asphalt composition was obtained in the same manner as in Example 1 except that the petroleum resin was not used.
[0365] Table 1 shows the evaluation results of the asphalt composition according to the first invention produced in each example.
[0366] Table 2 shows the evaluation results of the petroleum resin (B) according to the second invention produced in each example.
[0367] Table 3 shows the evaluation results of the hydrogenated petroleum resin (C) according to the third invention produced in each example.
[0368]
[0369] The results shown in Table 1 confirmed that the asphalt compositions according to the first invention of Examples 1 to 4 were less likely to peel off from the aggregate than the asphalt compositions of Comparative Examples 1 and 2, and had improved water resistance as an asphalt composite material.
[0370] [Table 2]
[0371] Table 2: Petroleum resin (B) according to the second invention
[0372]
[0373] The results shown in Table 2 confirm that the asphalt compositions obtained using the petroleum resin (B) according to the second invention in Examples 3 and 4 are less likely to peel off from the aggregate than the asphalt compositions in Comparative Examples 1 and 2, and have improved water resistance as an asphalt composite material.
[0374] [Table 3]
[0375] Table 3: Hydrogenated petroleum resin (C) according to the third invention
[0376]
[0377] The results shown in Table 3 confirm that the asphalt compositions obtained in Examples 2 and 4 using the hydrogenated petroleum resin (C) according to the third invention are less likely to peel off from the aggregate than the asphalt compositions of Comparative Examples 1 and 2, and have improved water resistance as an asphalt composite material.
Claims
1. An asphalt composition comprising a petroleum resin (A) and a straight-run asphalt, The petroleum resin (A) is a petroleum resin obtained by copolymerizing monomers and silanes, wherein the monomers include at least one cyclic olefin having an ethylenically unsaturated group selected from the group consisting of C5 fraction, C8 fraction, C9 fraction obtained by decomposing naphtha, and cyclopentadiene compounds. The petroleum resin (A) satisfies the following (a1) to (a2), (a1) contains 0.1% by mass or more and 10% by mass or less of silicon element in terms of silicon atoms, (a2) The weight average molecular weight (Mw) is 500 or more and 3,000 or less.
2. The asphalt composition according to claim 1, wherein The petroleum resin (A) satisfies the following (a3), (a3) The softening point is 70 to 150°C.
3. The asphalt composition according to claim 1 or 2, wherein The silanes have a structure represented by the following formula (1): Formula (1): CH2=CR-(COO) x (C n H 2n ) y SiR’3 In formula (1), R is a hydrogen atom or a methyl group; x and y are 0 or 1, wherein when x is 1, y is 1; n is an integer from 1 to 12; each R' is independently an alkoxy group, an aryloxy group, an arylalkyloxy group, an aliphatic acyloxy group, an amino group or a substituted amino group having 1 to 12 carbon atoms, or a lower alkyl group having 1 to 6 carbon atoms, wherein no more than two of the three R' groups are alkyl groups.
4. The asphalt composition according to any one of claims 1 to 3, wherein The silane is at least one selected from vinyltrimethoxysilane, vinyltriethoxysilane, and 3-(trimethoxysilyl)propyl methacrylate.
5. The asphalt composition according to any one of claims 1 to 4, wherein The monomers include dicyclopentadiene.
6. The asphalt composition according to any one of claims 1 to 5, wherein The petroleum resin (A) is a hydrogenated product.
7. The asphalt composition according to any one of claims 1 to 6, wherein The content of the petroleum resin (A) in the asphalt composition is 0.1% by mass or more and 5% by mass or less.
8. An asphalt composite material comprising the asphalt composition according to any one of claims 1 to 7 and aggregate, wherein the content of the asphalt composition is 1 to 20% by mass.
9. Petroleum resin (B), which is a petroleum resin (B) obtained by copolymerizing monomers and silanes. The monomers include at least one cyclic olefin having an ethylenically unsaturated group selected from the group consisting of C5 fraction, C8 fraction, C9 fraction obtained by decomposing naphtha and cyclopentadiene compounds. The petroleum resin (B) satisfies the following (b1) to (b2), (b1) contains 0.1% by mass or more and 10% by mass or less of silicon element in terms of silicon atoms, (b2) The weight average molecular weight (Mw) is 500 or more and 3,000 or less.
10. The petroleum resin (B) according to claim 9, wherein The petroleum resin (B) satisfies the following (b3), (b3) The softening point is 70 to 150°C.
11. The petroleum resin (B) according to claim 9 or 10, wherein The silanes have a structure represented by the following formula (1): Formula (1): CH2=CR-(COO) x (C n H 2n ) y SiR’3 In formula (1), R is a hydrogen atom or a methyl group; x and y are 0 or 1, wherein when x is 1, y is 1; n is an integer from 1 to 12; each R' is independently an alkoxy group, an aryloxy group, an arylalkyloxy group, an aliphatic acyloxy group, an amino group or a substituted amino group having 1 to 12 carbon atoms, or a lower alkyl group having 1 to 6 carbon atoms, wherein no more than two of the three R' groups are alkyl groups.
12. The petroleum resin (B) according to any one of claims 9 to 11, wherein The silane is at least one selected from vinyltrimethoxysilane, vinyltriethoxysilane, and 3-(trimethoxysilyl)propyl methacrylate.
13. The petroleum resin (B) according to any one of claims 9 to 12, wherein The monomers include dicyclopentadiene.
14. The petroleum resin (B) according to any one of claims 9 to 13, wherein The petroleum resin (B) is a hydrogenated product.
15. An asphalt composition comprising the petroleum resin (B) according to any one of claims 9 to 14 and straight-run asphalt.
16. The asphalt composition according to claim 15, wherein The content of the petroleum resin (B) in the asphalt composition is 0.1% by mass or more and 5% by mass or less.
17. An asphalt composite material comprising the asphalt composition according to claim 15 or 16 and aggregate, wherein the content of the asphalt composition is 1 to 20% by mass.
18. A hydrogenated petroleum resin (C) obtained by copolymerizing monomers containing at least one cyclic olefin having an ethylenically unsaturated group selected from the group consisting of a C5 fraction, a C8 fraction, a C9 fraction obtained by decomposing naphtha, and cyclopentadiene compounds, with silanes. The hydrogenated petroleum resin (C) satisfies the following (c1) to (c2), (c1) contains 0.1% by mass or more and 10% by mass or less of silicon element in terms of silicon atoms, (c2) The weight average molecular weight (Mw) is 500 or more and 3,000 or less.
19. The hydrogenated petroleum resin (C) according to claim 18, wherein The hydrogenated petroleum resin (C) satisfies the following (c3), (c3) The softening point is 70 to 150°C.
20. The hydrogenated petroleum resin (C) according to claim 18 or 19, wherein The silanes have a structure represented by the following formula (1): Formula (1): CH2=CR-(COO) x (C n H 2n ) y SiR’3 In formula (1), R is a hydrogen atom or a methyl group; x and y are 0 or 1, wherein when x is 1, y is 1; n is an integer from 1 to 12; each R' is independently an alkoxy group, an aryloxy group, an arylalkyloxy group, an aliphatic acyloxy group, an amino group or a substituted amino group having 1 to 12 carbon atoms, or a lower alkyl group having 1 to 6 carbon atoms, wherein no more than two of the three R' groups are alkyl groups.
21. The hydrogenated petroleum resin (C) according to any one of claims 18 to 20, wherein The silane is at least one selected from vinyltrimethoxysilane, vinyltriethoxysilane, and 3-(trimethoxysilyl)propyl methacrylate.
22. The hydrogenated petroleum resin (C) according to any one of claims 18 to 21, wherein The monomers include dicyclopentadiene.
23. An asphalt composition comprising the hydrogenated petroleum resin (C) according to any one of claims 18 to 22 and straight-run asphalt.
24. The asphalt composition according to claim 23, wherein The content of the hydrogenated petroleum resin (C) in the asphalt composition is 0.1% by mass or more and 5% by mass or less.
25. An asphalt composite material comprising the asphalt composition according to claim 23 or 24 and aggregate, wherein the content of the asphalt composition is 1 to 20% by mass.
Citation Information
Patent Citations
Silane-containing compound and modified hydrogenated petroleum resin
WO2021161672A1